O livro didático de língua portuguesa nas salas de aula do sistema modular de ensino - SACRAMENTO, Arinéia Ferreira (2019)
This research aims to highlight the importance of a contextualized teaching of the contents of Portuguese Language, in the riverside regions, having as object of study the textbook. In an attempt to provide a reflection about the specificities they need be taken into consideration in the process of teaching and learning of the students of the field, in an education where the cultural context be valued in the education system, it was established, in this perspective, the following research question: "How teachers make the appropriation of the textbook of Portuguese Language in his classes, in Modular Teaching System, in the riverine locality of the Maúba River? It was used the case study research method, of the ethnographic type, namely: field research, applying questionnaires to four teachers of Portuguese Language, in a analysis of the answers of such questions; and, a detailed examination, of content of textbooks of the collection "Tecendo Linguagens", of the authors: Tânia Amaral Oliveira, Elizabeth Gavioli de Oliveira Silva, Cícero de Oliveira Silva e Luci Aparecida Melo Araújo, handled, from the 6th to the 9th year, at the country school, E. E. F. M. Nossa Senhora do Perpétuo Socorro, locus of research. As a theoretical foundation for the development of research, was used authors: Freire, (2004); Azzi (2000); PCNs (1998); LDB (2017); André (2005); Batista (2011); Rodrigues (2016); Brayner (2013); Azevedo (2012); Silva, Barros e Oliveira (2014), in a finding that the didactic material in study has limitations and can not meet the demands of the students of that locality.